The knowledge and attitude of patients about drugs they use - Vasović Lucija V.; Vasović Sara V.; Prodanović Dušan V.; Sabo Stanislav J.; Tomas-Petrović Ana D.; Vasović Velibor M.; Vukmirović Saša N. (Srpsko lekarsko drustvo, 2023)
Introduction: Although numerous effective drugs are available on the market, the effects of the therapy are often missing. Possible reasons include problems with access to health care, lack of compliance or a tendency to self-medicate. Aim: The aim of the study was to analyze the structure of the drugs dispensed to patients in the pharmacy, as well as the knowledge and attitudes of patients towards the drugs they use. Material and Methods: Research has been conducted in 2 pharmacies-pharmacy "Galenpharm" and pharmacy "Janković" in Kula, during 10 working days, 3 hours each day at randomly selected terms during March 2023. The number and type of drugs dispensed were recorded, and the respondents were interviewed according to a questionnaire prepared in advance. Results: During the observed period, the largest number of drugs dispensed was from the group of drugs used for the treatment of disorders of the cardiovascular system. In 89% of cases, patients take medicines according to the doctor's recommendation. Patient's knowledge about the correct use of medications, dosing and taking them in relation to meals is satisfactory. The knowledge about side effects of drugs and possible interactions is minimal, although over 90% of respondents read the instructions for the drug from the original packaging of the drugs. Conclusion: Patient's knowledge about the drugs they take is limited. By not taking medications correctly, patients are undertreated, regardless of the correct diagnosis and well-chosen medications. Their knowledge about drugs is a stumbling block in successful pharmacotherapy.